PENYELESAIAN SENGKETA PERTANAHAN MELALUI PROSES MEDIASI DI KANTOR PERTANAHAN KOTA BUKITTINGGI - Adityawarman, Adityawarman; Nurdin, Zefrizal; Rosari, Anton (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
In the issuance of Land Certificates through the Complete Systematic Land Registration (PTSL) program, there is a stage of the land measurement process carried out by surveyors at the Bukittinggi City Land Office, the land measurement process is a process of stages that basically occur in disputes over ownership of land rights, the community objects to the process of issuing Certificates both in the first land registration (routine) or Complete Systematic Land Registration (PTSL), because other people who object feel that their rights have been taken, in the process of issuing the certificate in the rules that the party who objects feels that their rights are being disturbed, the rights are in the form of ownership of the object or intersect with the boundaries of the land. This is the basis for the Author to conduct this research. The formulation of the problem in this study is 1. What are the factors that cause disputes in the process of issuing land title certificates through the Complete Systematic Land Registration (PTSL) at the Bukittinggi City Land Office? 2. How is the process of resolving disputes in the issuance of land title certificates through the Complete Systematic Land Registration (PTSL) at the Bukittinggi City Land Office? 3. What are the norms used as the basis for resolving disputes at the Bukittinggi City Land Office? The type of research used by the author is Empirical Jurisprudence, with the research location at the Bukittinggi City Land Office, The results of the study Mention the factors underlying the occurrence of defense 1). Lack of legal awareness: Lack of legal knowledge and awareness among the community can cause land disputes. 2). Lack of documentation: Lack of complete and accurate documentation of land rights can cause preservation. 3). Lack of communication: Lack of effective communication between the parties involved can lead to misunderstandings and disputes. The norms used as the basis for resolving disputes at the Bukittinggi City Land Office, in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 21 of 2021 concerning the Handling and Settlement of Land Cases, several important basic rules are explained regarding the procedures for handling and resolving land cases.